Pengembangan Media Augmented Reality Untuk Melatih Keterampilan Berpikir Abstrak Siswa SMA pada Materi Medan Magnet - Ricki Angga Rizti Yovan; Abd. Kholiq (University of Bengkulu, 2022)
The aim of this study is to describe the validity of learning media named MA FIA (Magnetic Field Fisika Augmented Reality) which is physics learning media material based on augmented reality to train the abstract thinking skills in magnetic field material of high school students. This research is development research with the DDD-E design model (Decide, Design, Develop, Evaluate). This research was limited to the validity of media only and not up to effectiveness and practically learning because of the spread of Covid-19 that carried out the PSBB. Validity in terms of learning, material, media and language. Three expert lecturers carried out the validation of this media. The data collection technique is a validation questionnaire method and analyzed by quantitative analysis method. Based on the results of the assessment conducted, the validity result of MA FIA in learning, material, language, media, and abstract thinking skill aspect were 92%, 94%, 95%, 93%, 92%. This result had very valid criteria and could be declared suitable as a learning medium to train the abstract thinking skills of high school students in magnetic field material. Also in the future research, this media can carried out the test of practically and effectiveness as teaching material.